Positioning Diverse Type IV Structures and Functions Within Class 1 CRISPR-Cas Systems - Taylor, Hannah N.; Laderman, Eric; Armbrust, Matt; Hallmark, Thomson; Keiser, Dylan; Bondy-Denomy, Joseph; Jackson, Ryan N. (Frontiers in Microbiology, 2021)
Diverse Type IV CRISPR systems encode CRISPR-associated (Cas) -like proteins that combine with small RNAs to form multi-subunit ribonucleoprotein complexes. However, the lack of Cas nucleases, integrases, and other genetic features commonly observed in most CRISPR systems has made it difficult to predict type IV mechanisms of action and biological function. Here we summarize recent bioinformatic and experimental advancements that collectively provide the first glimpses into the function of specific type IV subtypes. We also provide a bioinformatic and structural analysis of type IV-specific proteins within the context of multi-subunit (class 1) CRISPR systems, informing future studies aimed at elucidating the function of these cryptic systems.